Analysis Of Digital Marketing Implementation In Increasing Brand Awareness And Sales: A Case Study Of Pertiwi Village: Analisis Implementasi Pemasaran Digital dalam Meningkatkan Kesadaran Merek dan Penjualan: Studi Kasus Desa Pertiwi - Viko Rachmatullah Putra; Sri Mulyani; Arif Hidayat (Jurnal Bisnis dan Ekonomi, 2026)
Abstrak :The rapid development of digital technology has transformed consumer behavior within the tourism industry, necessitating accommodation service providers to adapt to more modern marketing strategies. Pertiwi Village, a provider of resort, villa, and convention services in Cisarua, Bogor, faces challenges in optimizing extensive market potential through digital platforms. This study aims to analyze the implementation of digital marketing conducted by Pertiwi Village and the extent to which this implementation can increase brand awareness and sales. The research methodology employed is descriptive qualitative with a case study approach. Primary data were obtained through in-depth interviews with the owner, management, digital marketing team, and consumers. Secondary data were gathered through direct observation of the company's digital assets (Instagram, TikTok, WhatsApp) and internal documentation related to sales reports and photographs of Pertiwi Village. Data validity was ensured through source and method triangulation.The results indicate that digital marketing implementation at Pertiwi Village focuses on utilizing Instagram and TikTok as primary channels for building brand awareness through visual content. However, challenges remain regarding content consistency, substance, and variety, as well as the synchronization between digital activities and optimal sales conversion. Furthermore, the TikTok platform has not been optimallyutilized by Pertiwi Village. Evaluation of success indicators shows that while there has been a significant increase in reach and engagement, sales growth strategies are still highly dependent on the responsiveness of the reservation team in handling inquiries via WhatsApp. This study provides recommendations including the renewal of created content, updates to digital marketing strategies, more optimal use of TikTok, as well as strengthening the integration of digital reservation systems and optimizing the use of paid advertising to reach more specific market segments.Research Objectives: :1. To identify the implementation of Digital Marketing (such as platforms, content types, and campaigns) that has been carried out by Pertiwi Village.2. To analyze the extent to which the implementation of Digital Marketing is able to increase Brand Awareness.3. To analyze how the implementation of Digital Marketing at Pertiwi Village contributes to the increase in Sales..Method : This study employs a descriptive qualitative research method with a case study approach. Primary data were obtained through interviews and direct observations at Pertiwi Village, while secondary data were sourced from supporting documents, such as photographs and company archives. Results : 1. The Digital Strategy: Building the Foundation Right now, Pertiwi Village is in the early but crucial stages of its digital journey. They’ve successfully tapped into the power of social media—specifically Instagram and TikTok—to act as their visual storefront. By using WhatsApp Business as their main communication hub, they’ve created a direct line to their customers. However, there’s still a big opportunity to level up. Moving beyond social media by building an official website and joining major travel platforms (OTAs) would take their professionalism and accessibility to the next level.2. Brand Awareness: Creating the "Homie" Identity One of the most impressive findings is how well the brand’s identity resonates with the public. Pertiwi Village has managed to carve out a reputation for being a "home away from home." Their digital content doesn't just look good; it’s honest. Because the peaceful vibe people see on their screens matches the actual experience at the villa, they’ve built a strong sense of trust. The high ratings on Google Maps further prove that their brand isn't just a logo—it’s a promise of quality that people actually recognize.3. Sales Performance: From Likes to Bookings When we look at the bottom line, the digital efforts are clearly paying off. We’ve seen a steady climb in bookings from 2023 through 2025, which tells us that their online presence is doing more than just gaining "likes"—it’s driving revenue. The sales process is very human-centric; it starts with a spark of interest on social media and ends with a conversation on WhatsApp. The takeaway here is that while the content catches the eye, it’s the quick and friendly response from the reservation team that ultimately closes the deal.